Treatment of Heart Failure with Sodium-glucose Cotransporter Type 2 Inhibitors - Riber Fabián Donoso Noroña; Nairovys Gómez Martínez; Adisnay Rodríguez Plasencia (Medisur, 2024)
Heart failure is a chronic disease that affects millions of people worldwide and is a leading cause of death. Sodium-glucose cotransporter type 2 inhibitors are a new class of drugs that have demonstrated cardiovascular benefits in patients with type 2 diabetes. The aim of the research was to gain insight into the efficacy of these drugs in the treatment of heart failure. To achieve this, a systematic search was conducted in the PubMed, Embase and Cochrane Library databases from 2018 to 2023. Randomized clinical trials comparing sodium-glucose cotransporter type 2 inhibitors with placebo or standard treatment in patients with heart failure were included. Ten clinical trials were identified that met the inclusion criteria. The results showed that the treatment significantly reduced the risk of hospitalization for heart failure and cardiovascular mortality compared with placebo or standard care, and that sodium-glucose cotransporter type 2 inhibitors improved cardiac function and reduced levels of B-type natriuretic peptide, a biomarker of cardiac stress. The results of this study support the inclusion of sodium-glucose cotransporter type 2 inhibitors in the treatment of heart failure in patients with or without type 2 diabetes. Further studies are needed to evaluate the long-term safety and efficacy of sodium-glucose cotransporter type 2 inhibitors in patients with heart failure.